2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944404
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of reaching and grasping kinematics and clinical measures of upper extremity function in persons with stroke related hemiplegia

Abstract: Timed measures of standardized functional tasks are commonly used to measure treatment effects in persons with upper extremity (UE) paresis due to stroke. The effectiveness of their ability to measure motor recovery has come into question because of their inability to distinguish between motor recovery and compensations. This paper presents three linear regression models generated from twelve kinematic measures collected during the performance of a two phase reach/grasp and transport /release activity as perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Recently, eye movements have been shown in stroke investigations to be a sensitive biomarker for cognitive and motor recovery ( 149 , 150 ). Additionally, poststroke patients display unique pathophysiologic phenotypes that may include tactile deficits ( 151 153 ), proprioceptive losses ( 154 , 155 ), hemiparesis and related motor synergies ( 156 158 ), and spasticity ( 159 161 ), which would suggest that these new sensory and motor “states” postinjury create new relationships between receptor and effector, requiring the need for re-integration ( 162 164 ).…”
Section: Impairment Of the Visuomotor Systemmentioning
confidence: 99%
“…Recently, eye movements have been shown in stroke investigations to be a sensitive biomarker for cognitive and motor recovery ( 149 , 150 ). Additionally, poststroke patients display unique pathophysiologic phenotypes that may include tactile deficits ( 151 153 ), proprioceptive losses ( 154 , 155 ), hemiparesis and related motor synergies ( 156 158 ), and spasticity ( 159 161 ), which would suggest that these new sensory and motor “states” postinjury create new relationships between receptor and effector, requiring the need for re-integration ( 162 164 ).…”
Section: Impairment Of the Visuomotor Systemmentioning
confidence: 99%
“…In addition, clinical assessment alone is insufficient to accurately evaluate the degree of impairment (Kim et al 2014). Recent studies of stroke rehabilitation using robotic devices have focused on kinematic movement measurement (Bosecker et al 2010;Kim et al 2014;Rohafza et al 2014). Kinematic movement measurement provides information regarding the ability to move the extremities through space (Rohafza et al 2014) and kinematic movement measurement is considered suitable to obtain specific and accurate motion data (Kim et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of stroke rehabilitation using robotic devices have focused on kinematic movement measurement (Bosecker et al 2010;Kim et al 2014;Rohafza et al 2014). Kinematic movement measurement provides information regarding the ability to move the extremities through space (Rohafza et al 2014) and kinematic movement measurement is considered suitable to obtain specific and accurate motion data (Kim et al 2014). In particular, according to recent studies of robot-assisted training for stroke patients, the combination of kinematic assessment and traditional clinical scales may allow for quantitative evaluation of motor impairment (Patterson et al 2011;van Dokkum et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Rohafza et al identified a multivariate model of four kinematic measures of movement collected in two virtual environments. This model predicted 56% of the variance ( p = 0.042) in Jebsen Test of Hand Function change as the result of a 2 week training intervention ( 49 ). Rohafza et al developed a similar multivariate model of measures of reach to grasp and object transport trajectory smoothness, hand opening, and trunk movement during a real object interaction test collected at baseline testing.…”
Section: Identifying Persons Likely To Benefit From Virtual Rehabilitmentioning
confidence: 99%